Respuesta :

Hi1315

Answer:

[tex]t = 1[/tex]

Step-by-step explanation:

[tex]16 - 2t = 5t + 9 \\ 16 - 9 = 2t + 5t \\ 7 = 7t \\ \frac{7}{7} = \frac{7t}{7} \\ t = 1[/tex]

hope this helps

brainliest appreciated

good luck! have a nice day!

Answer:

[tex]t=1[/tex]

Step-by-step explanation:

[tex]16-2t=5t+9[/tex]

[tex](+16)+(-2t)=(+5t)+(9)[/tex]

Add [tex]-16[/tex] and [tex]-5t[/tex] on both sides.

[tex](-2t)+(-5t)=(+9)+(-16)[/tex]

Add the like terms and evaluate.

[tex]-2t-5t=9-16[/tex]

[tex]-7t=-7[/tex]

[tex]7t=7[/tex]

[tex]t=7/7[/tex]

[tex]t=1[/tex]

ACCESS MORE